Development of interactive e-modules with stem approach using canva application to improve students' critical thinking ability in physics learning - Yunita Yunita; Rahma Diani; Hendri Noperi; Yessy Velina (JINoP (Jurnal Inovasi Pembelajaran), 2024)
This study aims to determine the feasibility,  response, and improvement of students' critical thinking skills towards learning using e-modules. This type of research is development research using Sugiyono's development model with 10 stages, namely potential and problems, data collection, product design, design validation, design revision, product trials, product revisions, usage trials, final product revisions, and mass production. The research was conducted at SMPN 6 Krui and MTsN 2 Lampung Tengah, with the research subjects being 88 students in class VIII. The instruments used in this study were validation sheets, student response questionnaire sheets and critical thinking ability tests. Based on the results of the study, the validation results of interactive e-modules with the STEM approach from material experts amounted to 92% and media experts amounted to 90% with the category very feasible to use in learning. The response of students to the attractiveness of the e-module in the field trial was 90% and the educator was 89% with a very interesting category. The results of improving students' critical thinking skills obtained N-gain 0.71 including the high category. Thus the e-module developed is categorized as feasible to use as an alternative physics teaching material